2015
DOI: 10.1007/s11682-015-9393-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain damage following prophylactic cranial irradiation in lung cancer survivors

Abstract: Long-term toxic effects of prophylactic cranial irradiation (PCI) on cognition in small cell lung cancer (SCLC) patients have not yet been well-established. The aim of our study was to examine the cognitive toxic effects together with brain structural changes in a group of long-term SCLC survivors treated with PCI. Eleven SCLC patients, who underwent PCI ≥ 2 years before, were compared with an age and education matched healthy control group. Both groups were evaluated using a neuropsychological battery and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 73 publications
3
29
1
Order By: Relevance
“…46 This explanation is also supported by the fact that similar WM changes are seen in long-term SCLC survivors. 32 Interestingly, these chemotherapy-related changes did not appear after platinum-based chemotherapy in the NSCLC group. We speculate that this distinct response to chemotherapy might be related to an increased susceptibility of SCLC to platinum-based toxicity.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…46 This explanation is also supported by the fact that similar WM changes are seen in long-term SCLC survivors. 32 Interestingly, these chemotherapy-related changes did not appear after platinum-based chemotherapy in the NSCLC group. We speculate that this distinct response to chemotherapy might be related to an increased susceptibility of SCLC to platinum-based toxicity.…”
Section: Discussionmentioning
confidence: 91%
“…On the basis of our results, patients with SCLC should be informed about the survival benefits of PCI and about the potential minor, but negative, effects of this therapy on cognitive functioning, with emphasis on their limited impact on quality of life. However, because of the permanent long-term cognitive and structural brain effects observed in our previous study of SCLC survivors treated with PCI, 32 we think that it is crucial to better identify upfront those patients in whom brain metastases will develop and those patients in whom they will not, so that we can safely avoid PCI in specific subgroups of patients and thereby elude the brain-toxic effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, cognitive impairment has been observed after chemotherapy, especially after combined whole-brain radiation therapy (8,9). An MRI study on patients with SCLC who received chemotherapy and PCI showed an association between long-term cognitive effects and structural brain changes (10).…”
Section: Chemotherapy Followed By Prophylactic Cranial Irradiation (Pci)mentioning
confidence: 99%